2015
DOI: 10.1111/iep.12145
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of CKs 14/20 is an early event in a rat model of multistep bladder carcinogenesis

Abstract: Cytokeratins (CKs) 14 and 20 are promising markers for diagnosing urothelial lesions and for studying their prognosis and histogenesis. This work aimed to study the immunohistochemical staining patterns of CK14/20 during multistep carcinogenesis leading to papillary bladder cancer in a rat model. Thirty female Fischer 344 rats were divided into three groups: group 1 (control); group 2, which received N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN) for 20 weeks plus 1 week without treatment; and group 3, which rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
3
9
0
Order By: Relevance
“…Both CK14 and CK20 were suggested to direct the aggravation of early urothelial carcinoma via the carcinoma in situ-driven pathway (13,17,21). In an animal model, altered expression of CK14 and CK20 corresponded to an early tumorigenic step of papillary urothelial carcinoma (22). Taken together, it would be reasonable to speculate that CK5/6negative/CK20-positive expression may represent a "second hit" to a primitive and aggressive CK14-positive papillary NMIUTUC.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Both CK14 and CK20 were suggested to direct the aggravation of early urothelial carcinoma via the carcinoma in situ-driven pathway (13,17,21). In an animal model, altered expression of CK14 and CK20 corresponded to an early tumorigenic step of papillary urothelial carcinoma (22). Taken together, it would be reasonable to speculate that CK5/6negative/CK20-positive expression may represent a "second hit" to a primitive and aggressive CK14-positive papillary NMIUTUC.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with this observation, Volkmer et al (19) and Ho et al (21) demonstrated that CK14 defined the most primitive/least differentiated basal-type urothelial carcinoma, which preceded the emergence of cancer cells expressing CK5 (intermediately differentiated) or CK20 (well-differentiated); further, CK14 expression marked the highly tumorigenic stem cell population. The increase in CK14 immunoreactivity was also observed at an early carcinogenesis stage, initiating the appearance of malignant lesions of the urinary bladder in a rat model (22). Moreover, CK14-positive urothelial carcinoma cells might have a predilection for chemoresistance (23).…”
Section: Introductionmentioning
confidence: 83%
“…12,21 The BBN-induced bladder tumors in mice or rat provide an opportunity to study the entire cascade of bladder cancer histogenesis in an immunocompetent context. 17 In comparison, xenograft experiments using in vitro cell lines can be done only in the context of immunodeficient animals and thus does not allow the same depth or detail into the pathogenesis of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…nitrosamine (BBN)-induced model is one of the most universally used model to study bladder carcinogenesis. 16,17 This model largely reminisces the multistep process that results in papillary urothelial neoplasms, 16,17 and allows in-depth study of the various steps of the process. In addition, the entire time span is short and thus feasible.…”
Section: Impact Statementmentioning
confidence: 99%
See 1 more Smart Citation